Novel approaches to breech force and bullet ricochet measurement for small arms fire - Mister, Michael (Cranfield University, 2020)
Danger zones are defined as an area on shooting ranges in which there is a high risk of harm. Risk driving factor for the size of the danger zone is the ammunition used, properties and ricochet behaviour of the specific ammunition design. The danger zone is of interest because a wrong estimation may lead to unwanted damage to the shooter’s far environment. The distant environment is less affected when it comes to weapon breech damage. However, the internal ballistic breech investigation during the process of firing is of high relevance for the safety considerations of the shooter. The purpose of this study is to show the influence of novel ballistic measurement devices on recent safety considerations. It is an experimental research study that looks at internal and terminal ballistic effects. The pushout force was investigated with a separately developed weapon breech, capable of measuring loads in a dynamic manner. The other investigated parameter was the ricochet danger which was also investigated with a device developed during the project. Both parameters lead to new safety considerations. During this thesis it became evident that the most relevant parameter for an accurate ricochet quantification is the momentum of the fragment. This measurement is possible thanks to a novel type of accelerometer equipped sensor plates developed in this work. The other main finding of this thesis is the fact that lubricated ammunition casings, irrespective of whether with water or oil lubrication, leads to a significant rise in pushout force. This pushout force is taken up by the breech and leads to safety-relevant rises of internal forces on the breech. Both measurement approaches need to be taken into account when it comes to future safety considerations of small arms fire.